The coastal fishes and fisheries of the Socotra Archipelago, Yemen. Issue 2 (30th April 2016) - Zajonz, Uwe; Lavergne, Edouard; Klaus, Rebecca; Krupp, Friedhelm; Aideed, Moteah Sheikh; Saeed, Fouad Naseeb
Abstract: The Socotra Archipelago is situated in the Gulf of Aden where tropical and "pseudo-temperate" conditions combine to create a unique marine ecosystem. The diversity, ecology, productivity and fisheries of the coastal fish assemblages are still relatively understudied and no update of the scientific knowledge existed. The islands support unique coastal and coral-associated fish assemblages in spite of the limited biogenic reef frameworks. Fish diversity is the highest among comparable Arabian eco-regions, and fish biomass productivity high too by Indian Ocean standards. The production of the once traditionally-managed small-scale fishery is severely declining and whether it is sustainable nowadays is extremely doubtful. At a time when Yemen is torn apart by a severe political and humanitarian crisis it is timely to review and update the current state of knowledge for scientists and managers, and thereby ease access to existing information, facilitating follow-on studies and evidence-based conservation and fisheries management. Highlights: Reviewing 35 years of largely unpublished fish research of a little known Arabian site Identification of the archipelago as most species rich comparable Arabian eco-region Fish biomass productivity is high and among the most productive Indian Ocean sites Artisanal fisheries effort and catch production is beyond sustainable limits